1997
DOI: 10.1002/(sici)1096-8644(199701)102:1<67::aid-ajpa6>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Culture as a stressor: A revised model of biocultural interaction

Abstract: Contemporary urban societies display in high relief the action of social stratification on human biology. Recent studies of biological responses to urban environments and of socioeconomically disadvantaged people indicate that culture allocates risks disproportionately to some individuals and groups within society through its constituent values and related patterns of behavior. Although risk allocation is present in all societies, it is very clear in urban environments within stratified societies where high ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Another important area of research that overlaps with biological anthropologists' interests in health lies in the link between food insecurity and chronic disease. Anthropologists are asking important questions about persistent challenges to population health and the pathways through which environmental context shapes biological outcomes, producing health disparities (Schell, 1997;Worthman and Kohrt, 2005;Kuzawa and Sweet, 2008;Hruschka, 2009). Chronic and infectious diseases are areas of interest for biological anthropologists, particularly the relationship between food insecurity and the incidence, prevalence, and progression of illness.…”
Section: Food Insecurity Infectious and Chronic Diseasementioning
confidence: 99%
“…Another important area of research that overlaps with biological anthropologists' interests in health lies in the link between food insecurity and chronic disease. Anthropologists are asking important questions about persistent challenges to population health and the pathways through which environmental context shapes biological outcomes, producing health disparities (Schell, 1997;Worthman and Kohrt, 2005;Kuzawa and Sweet, 2008;Hruschka, 2009). Chronic and infectious diseases are areas of interest for biological anthropologists, particularly the relationship between food insecurity and the incidence, prevalence, and progression of illness.…”
Section: Food Insecurity Infectious and Chronic Diseasementioning
confidence: 99%
“…Risk vulnerability represents the extent to which a given risk factor differentially relates to a particular outcome such as difficult child behavior. Several researchers have found that risk factors are associated with the most vulnerable members of society (Schell 1997). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, a concentration of physical and social risks is often focused on the most vulnerable population strata in many cultures (Evans 2001; Evans and Kantrowitz 2002; Schell 1997). Although there is a need to determine some invariant predictors that are usable in large scale research and intervention studies, it is equally vital to understand the context-specific aspects of risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to stimuli can increase intelligence quotient scores (32). Parental educational and stress levels, exposure to chronic noise, and the parent's daily living practices, such as the amount and type of attention given to the child, all contribute to learning and behavior patterns (34,35). Therefore, it is necessary for researchers to control for the differences in parental stimulation and social learning and the circumstances that can potentially modify intellect and developmental skills.…”
Section: Heterogeneity In Human Risk Factorsmentioning
confidence: 99%